2012
DOI: 10.1386/cjmc.3.1.33_1
|View full text |Cite
|
Sign up to set email alerts
|

Postcolonial incorporation of the different Other

Abstract: This article approaches the study of incorporation of 'visible minority' immigrants in Peterborough, Canada by insisting on framing their experiences in the legacies of colonialism, racial and ethnic formations, and processes that spill over nation-bound

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Although they minimized their personal experience of discrimination and its impact (Malhi & Boon, 2007), the perception of group discrimination led to retention of their cultural heritage (Taylor, Wright, Moghaddam, & Lalonde, 1990), and strengthened their identification with their ethnic communities (Shemirani & O'Connor, 2006). Foreign-born women reacted differently to personal encounters of racism based on the extent to which they had adopted mainstream Canadian culture and their knowledge of their ethnic group's historical experiences of racism (Ku, 2005(Ku, , 2012. Ng (1981) concluded that ethnicity is not intrinsic but that immigrants find themselves being given an ethnic identity on arriving in Canada.…”
Section: Cultural Transitioning and Negotiating Gender Roles By Forei...mentioning
confidence: 99%
See 1 more Smart Citation
“…Although they minimized their personal experience of discrimination and its impact (Malhi & Boon, 2007), the perception of group discrimination led to retention of their cultural heritage (Taylor, Wright, Moghaddam, & Lalonde, 1990), and strengthened their identification with their ethnic communities (Shemirani & O'Connor, 2006). Foreign-born women reacted differently to personal encounters of racism based on the extent to which they had adopted mainstream Canadian culture and their knowledge of their ethnic group's historical experiences of racism (Ku, 2005(Ku, , 2012. Ng (1981) concluded that ethnicity is not intrinsic but that immigrants find themselves being given an ethnic identity on arriving in Canada.…”
Section: Cultural Transitioning and Negotiating Gender Roles By Forei...mentioning
confidence: 99%
“…Ng (1981) concluded that ethnicity is not intrinsic but that immigrants find themselves being given an ethnic identity on arriving in Canada. Some visible minority foreign-born women position themselves in social spaces and express their identities by celebrating their ethnic or religious differences (Ku, 2012;Ruby, 2006) or through community involvement and activism within both their cultural communities and in the wider Canadian society (Tastsoglou & Miedema, 2003). Activism by visible minority foreign-born women played a significant role in their integration into Canadian society and served as a strategy to advocate for their ethnic communities in Canada (Miedema & Tastsoglou, 2000), and to resist racial discrimination (Ku, 2011(Ku, , 2013.…”
Section: Cultural Transitioning and Negotiating Gender Roles By Forei...mentioning
confidence: 99%
“…Further, multi-cultural subject making is built on discourses of alterity, wherein migrants are constructed as Others (Ku, 2012), existing "outside of western history and development" (Ku, 2012, p.6). Immigrants are educated to become the "multicultural Self" (Ku, 2012), who must negotiate their differences by either attempting to celebrate or erase their differences. Race, gender, and other power dynamics function as invisible yet everpresent markers in these discourses (Ku, 2012).…”
Section: Multicultural Subject-makingmentioning
confidence: 99%
“…Immigrants are educated to become the "multicultural Self" (Ku, 2012), who must negotiate their differences by either attempting to celebrate or erase their differences. Race, gender, and other power dynamics function as invisible yet everpresent markers in these discourses (Ku, 2012).…”
Section: Multicultural Subject-makingmentioning
confidence: 99%
“…Despite the reality that some migrants, particularly those from the Global South, have their own histories of colonialism and genocide, they often arrive in Canada with the illusion that fairness and equity are rooted in the values of the nation, when in fact, a history and legacy of colonialism and racism shows the opposite. Moreover, model minority theorists show how the construction of Asians as the desirable immigrant subject dismisses and delegitimizes the political claims of Indigenous peoples and non-conforming racialized others in the Global North (Park, 2011 ; Ku, 2012 ; Ngo, 2016a , b ). Within the model minority discourse, Asian peoples' successes are attributed to their “culture” which comprises hard work, self-reliance, and a focus on educational attainment.…”
Section: A Bit Of Herstorymentioning
confidence: 99%